RESPONSE TO POLICY OF ASSET REVALUATION AT BASIC AND CHEMICAL INDUSTRIES OF PUBLIC COMPANIES LISTED ON IDX IN 2015-2016 - Lely Indriaty , Gen Norman Thomas , Mahtubah Tubah , Engelwati Gani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to identify a response to asset revaluation policy based on PMK 191/PMK.010/2015. The asset revaluation policy is influenced by fixed asset intensity, company size, and profitability. The influence of these factors reflected a form of the response to asset revaluation policy. The employed research method is a quantitative method with the population of basic and chemical industries listed in Indonesia Stock Exchange (IDX) in the period of 2015 to 2016. A purposive sampling method with certain criteria was used to obtain 27 samples. Panel data was processed with Eviews9 to produce descriptive statistic, then the data were also tested with paired model, classical assumption, and hypothesis. Based on the paired model, a test of panel data obtained the best regression, namely fixed effect model as selected model with the regression equation: Y = 1.5721 + 4.5534X1 - 0.1102X2 + 2.4448X3 + ?. The result of t-test indicates that there is a significant influence on fixed asset intensity and company size to policy of asset revaluation and there is not a significant effect of profitability to asset revaluation policy. F test shows there is a significant influence of fixed asset intensity, company size and profitability simultaneously to policy of asset revaluation.